2016
DOI: 10.3402/qhw.v11.31934
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of national guidelines for the prevention and treatment of overweight and obesity in children and adolescents: a phenomenographic analysis of public health nurses’ perceptions

Abstract: ObjectiveTo explore and describe how public health nurses (PHNs) perceive the implementation of national guidelines for the prevention and treatment of overweight and obesity among children and adolescents in well-baby clinics and school health services.Design, sample, and measurementsAn explorative descriptive design was carried out through individual interviews with 18 PHNs and analysed according to the phenomenographic tradition.ResultsFour implementation strategies were described and assigned a metaphor: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(48 citation statements)
references
References 40 publications
(73 reference statements)
0
47
0
1
Order By: Relevance
“…PCPs' competence and perceived confidence, 23,32,33,44,49,70 role‐specific specialist education and training (e.g., pediatricians and pediatric nurses), 28,29,35,36,44,45,50,56,59,64 participation in obesity training 32,33,70 and breastfeeding training, 56,57 familiarity with guidelines 32,33 and greater experience of working with children and mothers 30,34,53,59,60 were all identified as facilitators of practice. PCPs who believed that their role in prevention of childhood obesity was important reported positive attitudes and intention to implement recommended practices 23,26,31,33,39,47,54,55,58,62,73 . Motivated PCPs used approaches that facilitated implementation; these included using tactful language to discuss potentially sensitive topics, focusing on overall health and well‐being rather than on weight, framing having overweight as a societal issue, and using the BMI chart to raise the topic of weight, diet and feeding practices 25,26,31,35,39–41,53,54 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PCPs' competence and perceived confidence, 23,32,33,44,49,70 role‐specific specialist education and training (e.g., pediatricians and pediatric nurses), 28,29,35,36,44,45,50,56,59,64 participation in obesity training 32,33,70 and breastfeeding training, 56,57 familiarity with guidelines 32,33 and greater experience of working with children and mothers 30,34,53,59,60 were all identified as facilitators of practice. PCPs who believed that their role in prevention of childhood obesity was important reported positive attitudes and intention to implement recommended practices 23,26,31,33,39,47,54,55,58,62,73 . Motivated PCPs used approaches that facilitated implementation; these included using tactful language to discuss potentially sensitive topics, focusing on overall health and well‐being rather than on weight, framing having overweight as a societal issue, and using the BMI chart to raise the topic of weight, diet and feeding practices 25,26,31,35,39–41,53,54 .…”
Section: Resultsmentioning
confidence: 99%
“…Deficits in knowledge about childhood obesity 6,7,13,21,22,25,29,30,32 Lack of familiarity with guideline content 7,18,[21][22][23]30,31,48 Lack of skills (counseling, communication) 7,13,18,19,[21][22][23]37 Lack of obesity prevention training 2,7,11,13,18,[21][22][23]29,31 Psychological capability Uncertainty about identifying infants at risk of developing obesity 7,13,14,16,21,29,30,34,37,38,46 Disagreement with guideline content/usefulness 1,8,9,13,…”
Section: Providing Anticipatory Guidancementioning
confidence: 99%
See 1 more Smart Citation
“…The nurses in this study revealed barriers or challenges at several levels: at the system level (implementation strategy, available resources, training and support, professional collaboration and referral options); at the individual school nurse level (perceived competence, attitudes and emotions); at the subject level (sensitivity of weight‐related issues); and at the professional level (scepticism about a BMI cut‐off of 25 as the starting point for interventions). In another Norwegian study, barriers to guideline implementation were identified at the individual nurse level (competence), the subject level (receptiveness of parents and children) and at the system level (resources, organisation, collaboration) (Nordstrand et al., ). In a Dutch study, the following barriers to implementation of a healthcare standard in childhood obesity were found: the sensitivity of the subject, lack of motivation on the part of the parents, previous negative experiences with lifestyle programmes, financial constraints and the lack of a multidisciplinary approach (Schalkwijk et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The Norwegian national guidelines appeared to be challenging to implement among staff in primary health care (Nordstrand, Fridlund, & Sollesnes, 2016;Riiser, Londal, Ommundsen, Misvaer, & Helseth, 2015). There is limited research on the implementation of guidelines to combat obesity; however, barriers to such interventions in primary health care have been reported (Quelly, 2014a;Regber, Marild, & Johansson Hanse, 2013;Steele et al, 2011).…”
Section: Introductionmentioning
confidence: 99%